Jezikovne prepreke pri zdravstveni negi tujegovorečih pacientov - Štante, Anja (Obzornik zdravstvene nege, 2018)
Introduction: Language barriers in nursing care of foreign language speaking patients affect the quality of healthcare and may hinder effective communication between the nurse and the patient. All patients regardless of their gender, nationality, race, ethnicity, religious affiliation or any other personal characteristic have the right to equal treatment in healthcare. The purpose of the study was to investigate how nurses deal with language barriers when nursing foreign language speaking patients.Methods: Qualitative research methodology was used. Semi structured interviews (n = 5) were conducted by purposive sampling. Conventional content analysis was used for data analysis and synthesis. Results: Content analysis gave three main categories: Contact with a foreign language speaking patient (1); dealing with the foreign language speaking patient (2) and solving communication problems with a foreign language speaking patient (3). Research showed that dealing with foreign language speaking patients causes distress for the participants in the study, although they still manage to maintain an emphatic therapeutic relationship and are aware of the dangers that language barriers can pose to the safety of the patient.Discussion and conclusion: Participants in the study pointed out that language barrier may represent a risk in securing the safety of patients. This area of interest has not been the subject of much research in Slovenia, so it would be necessary to conduct research into different aspects of language and cultural barriers, and to systematically regulate the treatment of foreign language speaking patients. This would significantly contribute to efficient communication and thus, safe and quality nursing care.
Keywords: bolnišnica; communication; hospital; interview; intervju; komunikacija; medicinske sestre; nurses